Cholic and Deoxycholic Acids Induce Mitochondrial Dysfunction, Impaired Biogenesis and Autophagic Flux in Skeletal Muscle Cells - Valero-Breton, M; Cabello-Verrugio, C; Tacchi, F; Abrigo, J; Orozco-Aguilar, J (BioMed Central Ltd, 2023)
Background: Skeletal muscle is sensitive to bile acids (BA) because it expresses the TGR5 receptor for BA. Cholic (CA) and deoxycholic (DCA) acids induce a sarcopenia-like phenotype through TGR5-dependent mechanisms. Besides, a mouse model of cholestasis-induced sarcopenia was characterised by increased levels of serum BA and muscle weakness, alterations that are dependent on TGR5 expression. Mitochondrial alterations, such as decreased mitochondrial potential and oxygen consumption rate (OCR), increased mitochondrial reactive oxygen species (mtROS) and unbalanced biogenesis and mitophagy, have not been studied in BA-induced sarcopenia. Methods: We evaluated the effects of DCA and CA on mitochondrial alterations in C2C12 myotubes and a mouse model of cholestasis-induced sarcopenia. We measured mitochondrial mass by TOM20 levels and mitochondrial DNA; ultrastructural alterations by transmission electronic microscopy; mitochondrial biogenesis by PGC-1α plasmid reporter activity and protein levels by western blot analysis; mitophagy by the co-localisation of the MitoTracker and LysoTracker fluorescent probes; mitochondrial potential by detecting the TMRE probe signal; protein levels of OXPHOS complexes and LC3B by western blot analysis; OCR by Seahorse measures; and mtROS by MitoSOX probe signals. Results: DCA and CA caused a reduction in mitochondrial mass and decreased mitochondrial biogenesis. Interestingly, DCA and CA increased LC3II/LC3I ratio and decreased autophagic flux concordant with raised mitophagosome-like structures. In addition, DCA and CA decreased mitochondrial potential and reduced protein levels in OXPHOS complexes I and II. The results also demonstrated that DCA and CA decreased basal, ATP-linked, FCCP-induced maximal respiration and spare OCR. DCA and CA also reduced the number of cristae. In addition, DCA and CA increased the mtROS. In mice with cholestasis-induced sarcopenia, TOM20, OXPHOS complexes I, II and III, and OCR were diminished. Interestingly, the OCR and OXPHOS complexes were correlated with muscle strength and bile acid levels. Conclusion: Our results showed that DCA and CA decreased mitochondrial mass, possibly by reducing mitochondrial biogenesis, which affects mitochondrial function, thereby altering potential OCR and mtROS generation. Some mitochondrial alterations were also observed in a mouse model of cholestasis-induced sarcopenia characterised by increased levels of BA, such as DCA and CA. © 2023, The Author(s).